NMR-based metabolomics analysis of organic and conventionally produced formula milk: preliminary results - Sara Corbu; Roberta Pintus; Angelica Dessì; Melania Puddu; Flaminia Cesare Marincola; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2019)
Proceedings of the 15th International Workshop on Neonatology and the 40th Congress UMEMPS (Union of Middle-Eastern and Mediterranean Pediatric Societies) • Cagliari (Italy) • October 24th-26th, 2019 • Children of the Middle-Eastern and Mediterranean area: we can do better! Guest Editors: Vassilios Fanos (Cagliari, Italy), Enver Hasanoğlu (Ankara, Turkey), Michele Mussap (Cagliari, Italy), Robert Sacy (Beirut, Lebanon), Elie Saliba (Tours, France), Salvatore Vendemmia (Aversa, Italy)   Nutrition in early life has important biological effects on immediate and lifetime health. In the light of these considerations, products such as specialized and standard infant formulas substitute for human milk have the potential to influence health outcomes differently depending on their composition. The recent knowledge of the long-term health beneﬁts of breast-feeding has addressed research toward the creation of formulas ever closer to the needs of the infant both in term of nutritional and functional compounds. In this regard, metabolomics has proved to be a promising tool to investigate the metabolic composition of breast milk and the differences compared with formula milk. To the best of our knowledge, no metabolomics studies on the compositional differences between organic and conventionally produced infant milk have been performed so far. To fill this gap, the aim of the present work was to use the 1H NMR-based metabolomics approach to compare the metabolome of organic and conventionally produced formula milk designed for fulfill infants' nutritional needs from birth to 12 months of age. Methionine content was found to be significantly (p = 0.001) higher in organic milk than in conventional formulas. For the sake of comparison, the metabolome of human milk samples was also analyzed. Although the study presents several limitations, our preliminary results further support the utility of metabolomics in research for infant nutrition.